Navigating Style: Exploring the Influence of Perceived Benefit and Perceived Ease of Use on Attitude Towards Use in AI-Enhanced Fashion E-Commerce - Istiqomah, Puji; Alfansi, Lizar (Program MM Universitas Surabaya, 2024)
Purpose: This research will focus on empirical analysis of the role of attitude towards use as a mediating variable between perceived benefit and perceived ease of use towards actual use. The research object is consumers who use e-commerce in Indonesia to purchase products in the fashion industry. Method: This research adopts a quantitative-explanatory approach, focusing on the consumer e-commerce within the fashion industry as its target population. The precise magnitude of this population remains indeterminate. Employing a purposive sampling technique, carrying 270 of respondents whom at least two purchases of fashion items through e-commerce. Result: Perceived Benefit and Perceived Ease of Use positive significant toward Actual Use. Furthermore, Perceived Benefit and perceived Ease of Use positive significant on Attitude Towards Use. Moreover, Attitude Towards Use positive significant on Actual Use. In terms of indirect hypothesis testing, Attitude Towards Use is partially mediating both the relation between Perceived Benefit and Perceived Ease of Use on Actual Use.